Cenegermin in Pediatric Neurotrophic Keratopathy. Issue 11 (November 2019) - Pedrotti, Emilio; Bonetto, Jacopo; Cozzini, Tiziano; Fasolo, Adriano; Marchini, Giorgio
Abstract : Purpose: We report a case of neurotrophic keratopathy (NK) arising after surgery for rhabdomyosarcoma of the jaw successfully treated with Cenegermin eye drops (Oxervate; Dompé Farmaceutici, Milan, Italy) in a 3-year-old boy. Methods: At the age of 1 year, the boy underwent surgery for rhabdomyosarcoma of the jaw, followed by radiotherapy. Subsequent NK was initially treated with preservative-free artificial tears, topical combination of dexamethasone 0.1% and netilmicin 0.3% (Netildex; Sifi, Catania, Italy), and moxifloxacin 0.5% (Vigamox; Alcon, Fort Worth, TX), followed by 10 cycles of a topical eye biopolymer containing a poly-carboxymethyl glucose sulfate solution (Cacicol; Theà, Clermont-Ferrand, France) and 4 amniotic membrane transplantations. Keratopathy was recalcitrant to therapy and tissue transplant. Therapy was switched to Cenegermin eye drops 6 times daily for 8 weeks. Results: Complete healing of the corneal epithelium was achieved at 3 weeks into treatment. Conclusions: Cenegermin was effective in restoring corneal integrity in this pediatric patient with NK.